Femtosecond laser correction of presbyopia (INTRACOR) in emmetropes using a modified pattern - Thomas, Bettina C.; Fitting, Anna; Auffarth, Gerd U.; Holzer, Mike P. (Journal of refractive surgery, 2012)
PURPOSE: To evaluate functional results and corneal changes after femtosecond laser correction of presbyopia (INTRACOR, Technolas Perfect Vision GmbH) in emmetropes using a modified treatment pattern over a 12-month period. METHODS: Twenty eyes from 20 emmetropic patients were treated with a modified intrastromal INTRACOR pattern consisting of 5 central rings and 8 radial cuts in a prospective, nonrandomized, uncontrolled, open, single-center, clinical study. Refraction, visual acuity, endothelial cell density, corneal pachymetry, total corneal power, and stray light were evaluated preoperatively and 1 (except endothelial cell density and stray light), 3, 6, and 12 months postoperatively. Patients filled out a subjective questionnaire at 12 months postoperatively. RESULTS: Comparison of preoperative versus 12-month postoperative median values revealed a significant improvement in uncorrected near visual acuity (UNVA) from 0.60 (20/80) to 0.10 logMAR (20/25) (P<.0001) and a significant decrease in corrected distance visual acuity (CDVA) from -0.10 (20/16) to 0.00 logMAR (20/20), which equals a median loss of one line (P=.0005). Fifteen percent of patients lost two lines of CDVA in the treated eye. Subjective spherical equivalent refraction remained unchanged at 0.00 diopters (D) (P=.194). After INTRACOR treatment, significant corneal steepening of 1.40 D and midperipheral flattening of 0.50 D occurred (both P<.0001). Corneal pachymetry at the thinnest point and endothelial cell density did not change significantly (P=.829 and P=.058, respectively). CONCLUSIONS: After 12 months, the modified INTRACOR pattern improved UNVA in emmetropic patients without inducing a myopic shift or significant changes in endothelial cell density or pachymetry.